Learning Pantun through Character-Educated Smart Pantun Web by Utilizing Local Wisdom - Sati Sati; Kuntoro Kuntoro (Proceedings Series on Social Sciences & Humanities, 2023)
The use of digital technology that is increasingly widespread in the world of education, spurred researchers to present the Pantun Learning Website presented in www.samrtpantun.com named "GET RID OF SAD WITH PANTUN". This research uses the R&D development model (Borg & Gall, 1983). The Borg and Gall development model has relatively long stages because there are 10 steps of implementation. This website is equipped with E-modules and interactive Quiz. The material about pantun is packaged in an e-module by utilizing local wisdom that contains character education. While the Quiz is a reflection of the material on the e-modules to measure the ability of students about the pantun material by looking at the scores displayed. The research subjects were fifth grade students in South Cilacap District. Data collection techniques in this study were observation and student response questionnaire. The results showed that students prefer to learn pantun through the web www.smartpantun.com. This is evidenced by the number of students who open the smartpantun website, and the learning outcomes of students on the quiz presented on average 87.27.